Pengembangan Teknik Ligapo untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa Inklusi pada Pembelajaran Tematik Sekolah Dasar - Agustin, Septiana (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2022)
This research aims to improve the creative thinking skills of inclusion students in Sudirman State Elementary School, Ambarawa Subdistrict. The work of innovation developed in this study is the ligapo technique that is folding, drawing, and cutting. A method designed to assist students with special needs in participating in learning activities together with regular students. The characteristic of inclusion students in class VI is slow learner (slow learning). Ligapo techniques were created to make it easier for students to accept and understand the subject matter. In addition, this technique also improves creative thinking skills for students. An important point in this innovative work is the impact that teachers have on the cultivation of concepts to students through folding, patterning, and cutting activities that are packed with fun and fun. The results showed that ligapo techniques can improve children's catch and reason in learning the material and memory to memorize the material. In fact, through this method inclusion students can improve their creative thinking skills. Inclusion students are able to develop folding and cutting techniques according to their creativity. Thus, this ligapo technique has a good impact on the development of creative ways of reasoning and thinking of inclusion students.